Analisis Dampak dan Regulasi Fintech Lending: Studi Kasus Pada Skandal Tanifund di Indonesia - Farbadi, Mayla Putri; Sianturi, Mouna Suez; Yadita, Devina; Nugraha, Rifansyah; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
In the fintech lending industry, especially peer-to-peer (P2P) lending platforms, violations against consumers often occur. Violations that often occur through P2P lending platforms that are not transparent and do not have adequate fund protection mechanisms. According to Article 1 number 2 of Law Number 8 of 1999 concerning Consumer Protection, a consumer is someone who uses goods and services available in the community. One of them is the case of TaniFund, a P2P lending platform that failed to pay massively in 2023. The method used in this study is the normative legal approach method because this legal research uses secondary data from primary legal materials and secondary legal materials. The results of this study state that in the consumer protection law, business actors must be aware that P2P lending consumers are protected by law, with the existence of this law it is hoped that P2P lending users will get adequate protection so that there are no more cases that harm P2P lending users.